Role of Lateral Pelvic Node Dissection in Rectal Cancer Surgery - Ozgur, Ilker; Gorgun, Emre (Clinics in Colon and Rectal Surgery, 2023)
The role of lateral pelvic lymph node dissection in the treatment of patients with locally advanced rectal cancer is a matter of controversy. Surgical practices in Korea and Japan have accepted this approach and are widely utilized; however, it is not routinely incorporated in the practice of countries in the Western hemisphere. This review will examine the role of lateral pelvic lymph node dissection.
Keywords: locally advanced rectal cancer; lateral pelvic lymph node; lymph node dissection; chemoradiotherapy